Insurance status is related to diffuse large B‐cell lymphoma survival. Issue 8 (28th January 2014) - Han, Xuesong; Jemal, Ahmedin; Flowers, Christopher R.; Sineshaw, Helmneh; Nastoupil, Loretta J.; Ward, Elizabeth
Abstract : BACKGROUND: Insurance status is associated with stage at diagnosis and treatment for non‐Hodgkin lymphoma (NHL), but no previous studies have addressed the relation between insurance status and survival for patients diagnosed with diffuse large B‐cell lymphoma (DLBCL), the most common subtype of NHL. METHODS: The authors analyzed survival among 3858 patients with DLBCL ages 18 to 64 years who were diagnosed in 2004 using data from the National Cancer Database, a nationwide, hospital‐based cancer registry. Kaplan‐Maier curves were compared between patients who had private insurance, Medicaid, and no insurance. Cox proportional hazards models were fitted to estimate hazard ratios (HRs) and 95% confidence intervals (CIs) for insurance controlling for age, sex, race, area‐level socioeconomic status, and potential mediators of the association between insurance status and survival, including stage at diagnosis, B‐symptoms, comorbidity, and treatment. RESULTS: After adjusting for sociodemographic factors, uninsured patients (HR, 1.39; 95% CI, 1.14‐1.70) and Medicaid‐insured patients (HR, 1.48; 95% CI, 1.23‐1.78) with DLBCL had lower survival compared with patients who had private insurance. This association was attenuated after adjusting for the potential mediators (for uninsured patients, HR, 1.18 [95% CI, 0.96‐1.44]; for Medicaid‐insured patients, HR, 1.27 [95% CI, 1.06‐1.53]). CONCLUSIONS: Uninsured and Medicaid‐insured patients with DLBCL had inferior survival compared with privately insured patients. These associations can be explained in part because uninsured/Medicaid‐insured patients who have DLBCL present with more advanced‐stage disease and comorbid illnesses and less commonly receive standard treatment. Access to affordable and adequate health care has the potential to improve survival for patients with DLBCL. Cancer 2014;120:1220–1227 . © 2014 American Cancer Society . Abstract : Uninsured and Medicaid‐insured patients with diffuse large B‐cell lymphoma have inferior survival compared with privately insured patients. These associations can be explained in part because uninsured/Medicaid patients with diffuse large B‐cell lymphoma present with more advanced‐stage disease and comorbid illnesses and less commonly receive standard treatment.